A Study on the Impact of Marketing Capability, Operations Capability, Environmental Capability and Diversification Strategy on the Performance of Hotel Industry in the UK - ZHANG, YUBO (2009)
Hotel industry has been an increasingly significant service industry across the whole world. The performance measurement method is crucial for hotels’ operations. This study examines the impacts of marketing capability, operations capability, environmental capability and diversification strategy on the business performance of hotel industry in the UK. Based on the financial archival data in the database and information obtained in the firm websites from 2004 to 2007, the investigation is carried out by using Data Envelopment Analysis (DEA), content analysis and regression analysis.